Children's Conceptual Development: A Long-Run Investigation - Yilmaz Saglam; Merve Ozbek (Journal of Education in Science, Environment and Health)
The study sought to investigate conceptual change process. It is specifically aimed to probe children's initial ideas and how or to what way those ideas alter in the long run. A total of 18 children volunteered and participated in the study. Individual interviews were conducted. The children were asked to define the concept of evaporation, explain how this phenomenon occurs, and picturize this natural occurrence. A total of five consecutive interviews were conducted. All interviews were recorded and later transcribed. The results indicated the children's initial ideas got enriched in time. In this course of enrichment, instead of replacing radically their former conception with the novel one, the children seemed to have reinterpreted the new idea within the framework of their prior knowledge. The novel conception further is mixed up with the elements from both old and new beliefs leading intermediate structures to emerge. The data further indicated the children seemed to have been unable to recognize the discrepancies between their personal knowledge system to that of the scientific. They seemed lacking meta-conceptual awareness preventing them to compare and contrast their personal views to that of scientifically accepted one.